Frictional Mechanics of Slow Earthquakes. Issue 9 (25th September 2018) - Leeman, J. R.; Marone, C.; Saffer, D. M.
Abstract: Tectonic faults slip in a wide range of modes that span from slow slip events to dynamic rupture. A growing body of observations document this spectrum of failure modes in many geologic settings. However, the physical mechanisms that dictate slow slip are not understood. Here we investigate the mechanics of slow slip using carefully controlled laboratory experiments that demonstrate a complete spectrum of slip modes: Laboratory stick‐slip event durations span from seconds to milliseconds, representing the equivalent of failure events that span the range from slow to dynamic earthquakes. The rheological critical stiffness k c is the primary control on the mode of slip, but higher‐order effects including velocity dependence of the frictional rate parameter and critical slip distance also play an important role. We also find that quasi‐dynamic instability results from negligible stress drop near the stability boundary, in tandem with negative feedback during slip acceleration rooted in the rate dependence of k c . Our work shows that a broad spectrum of slip behaviors can arise from a common frictional mechanism modulated by fault zone rheology and elastic properties. Key Points: Laboratory experiments illuminate a friction‐based explanation for the mechanics underlying the spectrum of fault slip Fault slip mode is dictated by the ratio of the loading stiffness to a critical rheological stiffness and varies with slip velocity Slow slip can be explained by velocity dependence of k c and rupture velocity by potential stress drop near the stability boundary